Analysis of The Impact of The Collapse of The Composite Stock Price Index on The Rate of Inflation in Indonesia - Sri Hutami Adiningsih S; Is Arianto Pratama (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
The decline in the Indonesia Composite Stock Price Index (IHSG) is often linked to economic instability and its potential impact on inflation. This study analyzes the relationship between IHSG decline and inflation in Indonesia using a qualitative approach through a literature review of previous studies, economic reports, and relevant theories in capital markets and macroeconomics. Findings suggest that a sharp IHSG decline can contribute to inflation through reduced investment, currency depreciation, and decreased investor confidence, affecting price stability. Additionally, global economic dynamics and monetary policy significantly influence this relationship.This study provides insights for policymakers and market participants to understand stock market fluctuations’ impact on the national economy and develop adaptive strategies to navigate economic uncertainties.